1995
DOI: 10.1074/jbc.270.8.4108
|View full text |Cite
|
Sign up to set email alerts
|

High Level Expression and Characterization of the Mitochondrial Citrate Transport Protein from the Yeast Saccharomyces cerevisiae

Abstract: The gene encoding the mitochondrial citrate transport protein (CTP) in the yeast Saccharomyces cerevisiae has been identified, and its protein product has been overexpressed in Escherichia coli. The expressed CTP accumulates in inclusion bodies and can be solubilized with sarkosyl. Approximately 25 mg of solubilized CTP at a purity of 75% is obtained per liter of E. coli culture. The function of the solubilized CTP has been reconstituted in a liposomal system where both its kinetic parameters (i.e. Km = 0.36 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
152
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(155 citation statements)
references
References 42 publications
3
152
0
Order By: Relevance
“…Thus, it has been purified (6, 7), kinetically characterized (8), cloned (9), and overexpressed (10). More recently we have extended our studies of the CTP to the yeast homologue of the higher eukaryotic protein (11). An advantage afforded by the yeast mitochondrial CTP is that following overexpression in Escherichia coli and subsequent isolation, CTP function can be reconstituted with high specific activity.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, it has been purified (6, 7), kinetically characterized (8), cloned (9), and overexpressed (10). More recently we have extended our studies of the CTP to the yeast homologue of the higher eukaryotic protein (11). An advantage afforded by the yeast mitochondrial CTP is that following overexpression in Escherichia coli and subsequent isolation, CTP function can be reconstituted with high specific activity.…”
mentioning
confidence: 98%
“…2 Moreover, we have demonstrated that upon isolation, both the isolated wild-type and Cys-less CTPs exist as functional dimers. 3 Based on hydropathy analysis, each monomer of the homodimer is predicted to contain six membrane-spanning domains (11).…”
mentioning
confidence: 99%
“…Besides the rat, CiC cDNA has been isolated and sequenced from a variety of species (15,38,39). Palmieri and coworkers (40) determined the complete sequence of the human Cic gene.…”
Section: Isolation Of Cic Cdnamentioning
confidence: 99%
“…CiC was first discovered in liver by Chappel and Haarhoff (9), so far different groups have purified this carrier to homogeneity from hepatic mitochondria of rat (10)(11)(12), bovine (13), eel (14), yeast (15), and maize (16). The first purification of CiC from rat-liver mitochondria was carried out in the presence of the nonionic detergent Triton X-100 followed by chromatography on hydroxyapatite/celite (10).…”
Section: Purified and Reconstituted Cicmentioning
confidence: 99%
“…Eukaryotes typically express Ϸ30-40 distinct MCF proteins, and although substrates for many have been identified [e.g., components of the tricarboxylic acid cycle, ADP͞ATP, flavins, etc. (24)(25)(26)], the substrates for the bulk of MCF transporters are unknown. In addition to the MCF proteins, 10 ATP-binding cassette transporters, 6 P-type ATPases, and 3 other transporters were tested for their effects on SOD2 activity (Table 1).…”
Section: An Mcf Protein Is Required For Manganese Activation Of Sod2 mentioning
confidence: 99%